3D Printing in Oral and Maxillofacial Surgery - Chakravarthy, Dr.Chitra; Bijja, Sushmitha; karthik, Aaron; Patil, Pramod; Mohd.akbar, Tabassum (International Journal of Innovative Research in Medical Science, 2023)
Background: The Oral and maxillofacial surgery (OMFS) often involves complex facial deformities and pathologies that require precise treatment planning for optimal outcomes. Traditional approaches have limitations in achieving desired aesthetic and functional results. However, the emergence of virtual surgical planning (VSP) and 3D printing technology has revolutionized OMFS by offering accurate and predictable treatment outcomes. Objectives: This article provides an overview of the applications, workflow process, techniques, and biomaterials used in 3D printing technology in OMFS. It also discusses the benefits of 3D printing, including improved preoperative planning, surgical accuracy, reduced intraoperative time, and enhanced surgical outcomes. Methods: A comprehensive literature review was conducted to explore the applications of 3D printing technology in OMFS. The different 3D printing techniques, such as stereolithography, fused deposition modeling, material jetting, selective laser sintering, and digital light processing, were examined. The integration of 3D printing in tissue engineering and the use of biomaterials in 3D printing were also explored. Results: The integration of 3D printing in OMFS offers several advantages. It enables precise preoperative planning and simulation, resulting in improved surgical outcomes. The use of 3D-printed surgical guides and custom-made implants enhances surgical accuracy and reduces intraoperative time. Moreover, 3D printing facilitates the production of contour models and splints, further aiding in treatment planning and postoperative care.